Critical Period Hypothesis of Second Language Acquisition and Its Implications on the Optimal Starting Age of Foreign Language Teaching in China - Yan, Yan (Journal of Theory and Practice of Social Science, 2023)
There is a widely‐recognized belief held by a vast majority of people to learn a foreign language, that is, “the younger, the better”. However, in the field of SLA, researchers have been debating on the existence of the critical period. This paper firstly introduces what is the critical period hypothesis. Then, this paper summarizes the controversies about the critical period of SLA among different scholars at home and abroad. Finally, according to the different research results at home and abroad and the practice of foreign language teaching in China, this paper puts forward some enlightenment of the critical period hypothesis for SLA to the optimal starting age of foreign language teaching in China.